2020
DOI: 10.1002/hyp.13912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physico‐geographical factors and climate variability on flow intermittency in the rivers of water surplus zone

Abstract: Climate change is inevitably altering the hydrological regime of water bodies. The interest in changing behaviour of intermittent rivers is increasing in many countries. This research was focused on intermittent rivers (rivers which naturally, periodically cease to flow) in Lithuania. The purpose of this research was to provide an overview of flow intermittency phenomena according to available data in a historical period and to evaluate the impact of catchment geographical features and climate variability on z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…The central Lithuanian hydrological region will experience the greatest decline of runoff according to all projections and in both the near and far future periods. This finding corresponds with a previous study [51] that highlighted vulnerability and a high risk of an increasing number of rivers drying up in response to climate change in this particular hydrological region.…”
Section: Discussionsupporting
confidence: 93%
“…The central Lithuanian hydrological region will experience the greatest decline of runoff according to all projections and in both the near and far future periods. This finding corresponds with a previous study [51] that highlighted vulnerability and a high risk of an increasing number of rivers drying up in response to climate change in this particular hydrological region.…”
Section: Discussionsupporting
confidence: 93%
“…These findings broadly support the results of other studies, suggesting that the identified specifics of river catchments from different hydrological regions and climatic conditions help analyze and project extreme hydrological phenomena in the conditions of changing aridity [28,29,34,69,70]. SPI and RDI parameters showed that in most cases, the number of dry months and the minimum value of the index increased with an extension of the accumulation period.…”
Section: Discussionsupporting
confidence: 89%
“…This tendency is identified in the past and future due to specific conditions of river feeding sources (the smallest amount of precipitation and groundwater feeding in the C-LT region). This could be the reason why almost all Lithuanian intermittent rivers are located in this region [69]. In the future, the hydrological droughts are expected to be more extreme in the C-LT region, and the number of intermittent rivers may even increase.…”
Section: Discussionmentioning
confidence: 98%
“…Summer flows projections in the studied rivers showed a decreasing tendency [27,28]. The ongoing signs of climate change led to the investigation of intermittent rivers, which are particularly sensitive to any alterations in meteorological conditions or any anthropogenic disturbances [29].…”
Section: Introductionmentioning
confidence: 99%